2021
DOI: 10.1038/s41541-021-00420-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of multivalent mRNA vaccine candidates for seasonal or pandemic influenza

Abstract: Recent approval of mRNA vaccines for emergency use against COVID-19 is likely to promote rapid development of mRNA-based vaccines targeting a wide range of infectious diseases. Compared to conventional approaches, this vaccine modality promises comparable potency while substantially accelerating the pace of development and deployment of vaccine doses. Already demonstrated successfully for single antigen vaccines such as for COVID-19, this technology could be optimized for complex multi-antigen vaccines. Herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…Second, several studies demonstrated that combining multiple immune response to different epitopes can increase significantly the efficacy of vaccination [54][55][56][57][58] . The rise of mRNA vaccines 59,60 may facilitate the development of a new generation of multivalent vaccines that could use the pyramiding effect to increase their durability.…”
Section: Discussionmentioning
confidence: 99%
“…Second, several studies demonstrated that combining multiple immune response to different epitopes can increase significantly the efficacy of vaccination [54][55][56][57][58] . The rise of mRNA vaccines 59,60 may facilitate the development of a new generation of multivalent vaccines that could use the pyramiding effect to increase their durability.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Chivukula et al, demonstrated the applicability of the mRNA therapeutic platform for multivalent influenza vaccine creation [ 103 ]. Proof-of-concept experiments were successfully completed in mice and nonhuman primates (NHP).…”
Section: Universal Flu Vaccine Perspectivesmentioning
confidence: 99%
“…Each of the aforementioned methods can be delivered via a recently emerged mRNA vehicle platform, e.g., chimeric HA, predicted epitopic peptides, or a cocktail of various IAVs subtypes genome fragments may be inserted into an mRNA cassette. Moreover, multiple mRNA transcripts can be packaged and delivered as a combination with no differences in the impact on the magnitude of humoral immune response, compared with antigen delivered monovalently [ 103 ].…”
Section: Universal Flu Vaccine Perspectivesmentioning
confidence: 99%
“…To limit the number of animals needed, developers can co-encapsulate fluorescent protein-encoding mRNA and luciferase-encoding mRNA in a single LNP, which mimics multivalent mRNA vaccines [158] , [159] . Alternatively, it is also possible to encode an eGFP-Fluc fusion protein on a single mRNA instead [130] .…”
Section: Other Techniques That Could Reach Ema/fda Requirementsmentioning
confidence: 99%